An update on medium- and low-abundant blood plasma proteome of horse. (10th July 2017) - Lepczyński, A.; Ożgo, M.; Dratwa-Chałupnik, A.; Robak, P.; Pyć, A.; Zaborski, D.; Herosimczyk, A.
Abstract : The main objectives of the study were to: (1) deeply analyse the serum protein composition of Equus caballus, (2) assess the effectiveness of the high-abundant protein depletion and improve the concentration of medium- and low-abundant proteins. The analysis were performed on the blood plasma of three healthy part-Arabian mares. The implementation of two-dimensional electrophoresis and matrix-assisted laser desorption/ionisation – time of flight mass spectrometry allowed us to establish a horse plasma proteome map. Serum proteins were resolved at pH 4 to 7, followed by 12% SDS-PAGE. As a result 136 spots were successfully identified, representing the products of 46 unique genes. Of these, 22 gene products have not been previously identified in horse serum/plasma samples using proteomic tools. Gene ontology analysis showed that almost 30% of all identified gene products belong to the coagulation and complement cascades. These results can undoubtedly serve as a useful and prospective prerequisite for the future analysis of horse plasma proteome changes in different physiological and pathophysiological conditions. The use of the medium- and low-abundant protein enrichment tool increased their abundance and allowed us to identify a higher number of protein gene products. The highest depletion efficiency was observed for the most abundant plasma proteins, that is albumin, IgG heavy chains and serotransferrin.